TCDD exposure alters fecal IgA concentrations in male and female mice - Christine L. Foxx; Madeline R. Nagy; Aspen E. King; Dreycey Albin; Gregory K. DeKrey (BMC, 2022)
Abstract Background Activation of the aryl hydrocarbon receptor (AhR) can alter diurnal rhythms including those for innate lymphoid cell numbers, cytokine and hormone levels, and feeding behaviors. Because immune responses and antibody levels are modulated by exposure to AhR agonists, we hypothesized that some of the variation previously reported for the effects of AhR activation on fecal secretory immunoglobulin A (sIgA) levels could be explained by dysregulation of the diurnal sIgA rhythm. Methods C57Bl/6 J mice were exposed to peanut oil or 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD, 10 or 40 μg/Kg) and fecal sIgA levels were determined in samples collected every 4 h over 4 days. Results Fecal sIgA concentrations were not significantly different between light and dark phases of the photoperiod in either male or female mice, and there were no significant circadian rhythms observed, but TCDD exposure significantly altered both fecal mesor sIgA and serum IgA concentrations, in parallel, in male (increased) and female (biphasic) mice. Conclusions AhR activation can contribute to the regulation of steady state IgA/sIgA concentrations.